Observations of tropospheric NO2 using ground based MAX-DOAS and OMI measurements during the Shanghai World Expo 2010 - Chan, Ka Lok; Hartl, A.; Lam, Y. F.; Xie, P. H.; Liu, W. Q.; Cheung, H. M.; Lampel, J.; Pöhler, Denis; Li, A.; Xu, J.; Zhou, H. J.; Ning, Z.; et al. (Atmospheric environment, 2015)
During the Shanghai World Expo 2010 ground based Multi-Axis Differential Optical Absorption Spectroscopy (MAX-DOAS) measurements of tropospheric nitrogen dioxide (NO2) were performed to investigate the effects of emission control measures during that time. In this study we measured NO2 using four identical MAX-DOAS instruments in Shanghai from April 2009 to November 2010. We combined our MAX-DOAS data, the Ozone Monitoring Instrument (OMI) satellite observations and meteorological information from the National Centers for Environmental Prediction final reanalysis data (NCEP FNL) in order to investigate the spatial distribution of NO2 over Shanghai and the effects of emission control measures during the Expo. In general, the comparison of cloud screened MAX-DOAS data and OMI observations are in good correlation (Pearson correlation coefficient between 0.67 and 0.93 for the four measurement stations). In addition, we compared the MAX-DOAS and OMI NO2 data from the Shanghai Expo in 2010 to the same time of the year in 2009. The results show that the NO2 columns were reduced up to ∼ 30% in the area of central Shanghai during the Expo but no significant reduction of NO2 levels was found in the nearby industrial area. The overall NO2 reduction from May, July and September 2010 ranged from 7.5% to 14.5%, which is comparable to observations in previous studies. Our results revealed that the NO2 reduction was mainly achieved by emission control policies on transportation sources in the city rather than the controls from nearby provinces.